2016
DOI: 10.1371/journal.pone.0164231
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Stromal Re-Distribution of Primary Cilia during Pancreatic Carcinogenesis

Abstract: BackgroundThe Hedgehog (HH) pathway is a mediator in pancreatic ductal adenocarcinoma (PDAC). Surprisingly, previous studies suggested that primary cilia (PC), the essential organelles for HH signal transduction, were lost in PDAC. The aim of this study was to determine the presence of PC in human normal pancreas, chronic pancreatitis, and during carcinogenesis to PDAC with focus on both epithelia and stroma.MethodsPC were analyzed in paraffin sections from normal pancreas, chronic pancreatitis, intraductal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Based on our data and the results of a previous study (Deng et al, 2018), primary cilia appear to be suppressors of PDAC proliferation. This notion is supported by the fact that PDAC cells gradually lose primary cilia over time (Schimmack et al, 2016;Deng et al, 2018). Conversely, a clinical report showed that the presence of primary cilia correlates with poor prognosis of PDAC patients (Emoto et al, 2014), suggesting the possibility of a promotive role of primary cilia.…”
Section: Discussionmentioning
confidence: 97%
“…Based on our data and the results of a previous study (Deng et al, 2018), primary cilia appear to be suppressors of PDAC proliferation. This notion is supported by the fact that PDAC cells gradually lose primary cilia over time (Schimmack et al, 2016;Deng et al, 2018). Conversely, a clinical report showed that the presence of primary cilia correlates with poor prognosis of PDAC patients (Emoto et al, 2014), suggesting the possibility of a promotive role of primary cilia.…”
Section: Discussionmentioning
confidence: 97%
“…As another example, in the pancreas , cancer formation commonly goes through set stages in which ductal acini typically convert through pancreatic intraepithelial neoplasia precursor stages (PanIN stages 1–3) to overt pancreatic ductal adenocarcinomas (PDACs). Although normal pancreatic ductal epithelia, islet cells, and centroacinar cells, are highly ciliated, cilia are sharply reduced during formation of PDACs, from the earliest precursor stages 60 , and in cases of the pre-neoplastic condition of pancreatitis 61 . Human PDACs have high levels of intratumoural heterogeneity, with some cancer cells more differentiated and some less so; a study of clinical outcomes showed that residual ciliation of cancer cells segregated to the well-differentiated areas (Figure 4A), and a higher level of cancer cell ciliation was prognostic of improved overall survival 62 .…”
Section: Ciliation Impacts Cancer Pathogenesis and Response To Therapymentioning
confidence: 99%
“…Instead, it was more recently demonstrated that primary cilia in the epithelium are gradually lost during pancreatic carcinogenesis, and this loss is accompanied by gain of primary cilia in the surrounding stroma (Table I). Moreover, the BxPc3, Capan1, MiaPaCa2, and PANC-1 PDAC cell lines do not lose primary cilia under conditions of nutrient or oxygen deprivation (27). At the molecular level, these studies demonstrated that, by inhibiting the downstream effectors of the K-Ras pathway, mitogen-activated protein kinase kinase (MEK) and phosphoinositide 3-kinase (PI3K), ciliogenesis was fully restored, suggesting that K-Ras may be involved in the regulation of ciliogenesis in PDAC (15,28).…”
Section: Pdac and Ciliummentioning
confidence: 95%